Early Critical Thinking in a Mandarin-Speaking Child: An Exploratory Case Study - Xuemei Shao; Ruying Qi; Satomi Kawaguchi; Hui Li (MDPI AG, 2022)
Critical thinking in children is a growing concern for early childhood educators; however, few studies have examined children's critical thinking in an out-of-class context. This case study aimed toward filling this research gap by examining the critical thinking of a Mandarin-speaking child aged 5 years and 8 months in an out-of-class context. The child's natural utterances produced in free conversation and story-readings have been audio- and video-taped twice a week over two months. The recordings have been transcribed and analyzed according to the Delphi Report and 'level of questions' to examine the child's critical thinking level. Findings revealed that the child demonstrated critical thinking, and two indicators, 'spontaneous statements' and 'continuous questions', reflected children's critical thinking level. It also found that these categories were reasonable and practical to identify young children's critical thinking levels.